Coming full circle : spirituality and wellness among native communities in the Pacific Northwest - Crawford O'Brien, Suzanne J. (Lincoln, Nebraska : University of Nebraska Press, 2013)
"Coming Full Circle is an interdisciplinary exploration of the relationships between spirituality and health in several contemporary Coast Salish and Chinook communities in western Washington from 1805 to 2005. Suzanne Crawford O'Brien examines how these communities define what it means to be healthy, and how recent tribal community-based health programs have applied this understanding to their missions and activities. She also explores how contemporary definitions, goals, and activities relating to health and healing are informed by Coast Salish history and also by indigenous spiritual views of the body, which are based on an understanding of the relationship between self, ecology, and community. Coming Full Circle draws on a historical framework in reflecting on contemporary tribal health-care efforts and the ways in which they engage indigenous healing traditions alongside twenty-first-century biomedicine. The book makes a strong case for the current shift toward tribally controlled care, arguing that local, culturally distinct ways of healing and understanding illness must be a part of contemporary Native healthcare. Combining in-depth archival research, extensive ethnographic participant-based field work, and skillful scholarship on theories of religion and embodiment, Crawford O'Brien offers an original and masterful analysis of contemporary Native Americans and their worldviews."--
Machine generated contents note: pt. One Locations -- 1. Theoretical Orientation: Embodied Subjectivity and the Self in Motion -- pt. Two Illness, Healing, and Missionization in Historical Context -- 2. "The Fact Is They Cannot Live": Euroamerican Responses to Epidemic Disease -- 3. "Civilization Is Poison to the Indian": Missionization, Authenticity, and the Myth of the Vanishing Indian -- pt. Three Restoring the Spirit, Renewing Tradition -- 4. "A Good Christian Is a Good Medicine Man": Changing Religious Landscapes from 1804 to 2005 -- 5. Both Traditional and Contemporary: The South Puget Intertribal Women's Wellness Program -- 6. Coming Full Circle: Defining Health and Wellness on the Shoalwater Bay Indian Reservation -- pt. Four Person, Body, Place -- 7. "Rich in Relations": Self, Kin, and Community -- 8. Healthy Self: Embedded in Place -- 9. "A Power Makes You Sick": Illness and Healing in Coast Salish and Chinook Traditions.
Includes bibliographical references and index.
Print version record.
Keywords: Coast Salish Indians -- Religion; Coast Salish Indians -- Health and hygiene; Coast Salish Indians -- Medicine; Indigenous peoples -- Ecology -- Northwest, Pacific; Traditional medicine -- Northwest, Pacific; SOCIAL SCIENCE -- Ethnic Studies -- Native American Studies; RELIGION -- Ethnic & Tribal; HEALTH & FITNESS -- Healing; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Indigenous peoples -- Ecology; Traditional medicine; Pacific Northwest; Electronic books